Features of school socialization in modern society - Myhailuk, О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with the specifics of the process of individual socialization. The basic approaches concerning periodization of the process are mentioned. There are basic psychological and social factors and conditions that influence the effectiveness of socialization in this article. The main features of school socialization of children living in urban and rural areas were examined. The results of studies devoted to comparison of the effectiveness of socialization in various localities are given.
Keywords: socialization; identity; society; adaptation; school